Young Adult Tourists’ Perspective on Family Tourism and The Role of Social Media in Memory Formation - Fitriya Nurul Azizah; Heri Puspito Diyah Setiyorini (International Journal of Multidisciplinary Sciences and Arts, 2026)
Family tourism in university students’ lives is increasingly shaped by digitalization, social media self-representation, and changing family relationships influenced by mobile lifestyles and technology. Although family travel is closely connected to social media use, students’ perspectives on how travel experiences become memories remain underexplored. This study examines the meaning of family tourism for university students and the role of social media in shaping, reinforcing, and reframing travel memories. Using an exploratory qualitative approach, data were collected through semi-structured online focus group discussions with 24 university students. The data were transcribed and analyzed using the Miles–Huberman–Saldaña framework with NVivo. Findings indicate that students perceive family tourism as meaningful moments of togetherness that strengthen emotional bonds and create lasting memories through shared interactions and experiences. Social media influences travel experiences before, during, and after trips, functioning as both a planning tool and a digital archive of memories. Overall, family tourism provides an important space for strengthening family relationships and memory formation, while social media enriches and shapes how these experiences are remembered and interpreted.